An Undiagnosed Paraganglioma in a 58-Year-Old Female Who Underwent Tumor Resection - William C. Fox; Matthew Read; Richard E. Moon; Eugene W. Moretti; Brian J. Colin (Case Reports in Anesthesiology)
Paragangliomas and pheochromocytomas are rare neuroendocrine tumors that can have high morbidity and mortality if undiagnosed. Here we report a case of an undiagnosed paraganglioma in a 58-year-old female who underwent tumor resection. The patient became severely hypertensive intraoperatively with paroxysmal swings in blood pressure and then later became acutely hypotensive after tumor removal. She was managed in the surgical intensive care unit (SICU) postoperatively and discharged from the hospital without acute complications. We briefly discuss the epidemiology, clinical presentation, perioperative management, and possible complications of these tumors to assist healthcare providers if one were to encounter them.